Diabetes screening: a pending issue in hypertense/obese patients - Armina Sepehri; Antonio Palazón-Bru; Vicente Francisco Gil-Guillén; Dolores Ramírez-Prado; Felipe Navarro-Cremades; Ernesto Cortés; María Mercedes Rizo-Baeza (PeerJ, 2015)
The literature about possible cardiovascular consequences of diagnostic inertia in diabetes is scarce. We examined the influence of undetected high fasting blood glucose (FBG) levels on the cardiovascular risk and poor control of cardiovascular risk factors in hypertensive or obese patients, with no previous diagnosis of diabetes mellitus (i.e., diagnostic inertia). A cross-sectional study during a preventive program in a Spanish region was performed in 2003–2004. The participants were aged ≥40 years and did not have diabetes but were hypertensive (n = 5, 347) or obese (n = 7, 833). The outcomes were high cardiovascular risk (SCORE ≥5%), poor control of the blood pressure (≥140/90 mmHg) and class II obesity. The relationship was examined between FBG and the main parameters, calculating the adjusted odd ratios with multivariate models. Higher values of FBG were associated with all the outcomes. A more proactive attitude towards the diagnosis of diabetes mellitus in the hypertensive and obese population should be adopted.